2017
DOI: 10.3389/fpls.2017.00817
|View full text |Cite
|
Sign up to set email alerts
|

Roles, Regulation, and Agricultural Application of Plant Phosphate Transporters

Abstract: Phosphorus (P) is an essential mineral nutrient for plant growth and development. Low availability of inorganic phosphate (orthophosphate; Pi) in soil seriously restricts the crop production, while excessive fertilization has caused environmental pollution. Pi acquisition and homeostasis depend on transport processes controlled Pi transporters, which are grouped into five families so far: PHT1, PHT2, PHT3, PHT4, and PHT5. This review summarizes the current understanding on plant PHT families, including phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
113
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 134 publications
(191 reference statements)
5
113
0
Order By: Relevance
“…The PHT1 family is the largest one which includes nine genes in Arabidopsis (AtPHT1s), 25 in B. rapa (BrPHT1s), 8 B. oleracea (BoPHT1s) and 44 in B. napus (BnaPHT1s); the PHT2 family contained one AtPHT2 gene, two BrPHT2s, two BoPHT2s and four BnaPHT2s; the PHT3 family included three AtPHT3s, five BrPHT3s, four BoPHT3s and 10 BnaPHT3s; the PHT4 family was consisted of six AtPHT4s, seven BrPHT4s, six BoPHT4s and 13 BnaPHT4s; while the PHT5 family contained three AtPHT5s, three BrPHT5s, one BoPHT5 gene and nine BnaPHT5s (Figure 1). Consistent with previous studies [33], the PHT1 family could be further classified into two groups, where group I composed of 11 BnaPHT1s, seven BrPHT1s and five BoPHT1s that were homologous to AtPHT1.8 and AtPHT1.9; group II contained 33 BnaPHT1s, 18 BrPHT1s and three BoPHT1s that were homologous to AtPHT1.1-AtPHT1.7. Similarly, the PHT4 family might be classified into five groups (Group I-V) ( Figure 1 Physicochemical property analysis showed that the molecular weight (MW) of candidate BnaPHT proteins (BnaPHTs) ranged from19.20-78.90 kDa, the isoelectric point (IP) is 5.44-10.01 (Table S1).…”
Section: Phylogenetic Analysis Of B Napus Pht Gene Familysupporting
confidence: 85%
See 1 more Smart Citation
“…The PHT1 family is the largest one which includes nine genes in Arabidopsis (AtPHT1s), 25 in B. rapa (BrPHT1s), 8 B. oleracea (BoPHT1s) and 44 in B. napus (BnaPHT1s); the PHT2 family contained one AtPHT2 gene, two BrPHT2s, two BoPHT2s and four BnaPHT2s; the PHT3 family included three AtPHT3s, five BrPHT3s, four BoPHT3s and 10 BnaPHT3s; the PHT4 family was consisted of six AtPHT4s, seven BrPHT4s, six BoPHT4s and 13 BnaPHT4s; while the PHT5 family contained three AtPHT5s, three BrPHT5s, one BoPHT5 gene and nine BnaPHT5s (Figure 1). Consistent with previous studies [33], the PHT1 family could be further classified into two groups, where group I composed of 11 BnaPHT1s, seven BrPHT1s and five BoPHT1s that were homologous to AtPHT1.8 and AtPHT1.9; group II contained 33 BnaPHT1s, 18 BrPHT1s and three BoPHT1s that were homologous to AtPHT1.1-AtPHT1.7. Similarly, the PHT4 family might be classified into five groups (Group I-V) ( Figure 1 Physicochemical property analysis showed that the molecular weight (MW) of candidate BnaPHT proteins (BnaPHTs) ranged from19.20-78.90 kDa, the isoelectric point (IP) is 5.44-10.01 (Table S1).…”
Section: Phylogenetic Analysis Of B Napus Pht Gene Familysupporting
confidence: 85%
“…In contrast, the majority of the PHT5 family are located on the cell membrane and vacuole except for one (BnaPHT5.2), which was located on the cell membrane and chloroplast. The diverse subcellular localization features (Table S1) of these five families were highly consistent with the functional diversity of their homologs in plants [33].…”
Section: Phylogenetic Analysis Of B Napus Pht Gene Familysupporting
confidence: 62%
“…And the increase of nitrogen and phosphorus may contribute to regulate the integrity of photosynthetic materials and membranes, which may minimize the effects of drought stress on the growth and development of bamboo plants [22]. Additionally, it was reported that the root hair of barley plays a crucial role in relieving water and phosphorus stress [23]. Furthermore, the interaction of nutrients in the plant had a major in uence on the nutrient response genes that regulate root structure and transcriptional regulation in the root [24].…”
Section: Introductionmentioning
confidence: 99%
“…The higher the intake of nutrients by a root system according to the growth requirements of a plant and higher is the nutrients transport and the metabolic activities. Uptake and translocation of nutrients play essential roles in plant for signal transduction, growth, and development [20]. In this study, it might be that types of salts for stress affected sulphur and phosphorus acquisition by interfering with K + uptake by carriers and channels as revealed by [21].…”
Section: Effect Of Types Of Salt Stress On Sulphur and Phosphorus Conmentioning
confidence: 99%